Keats, Sextus Empiricus, and Medicine. Issue 2 (July 2016) - Ou, Li
Abstract : This essay discusses Keats's affinity with Pyrrhonian scepticism as recorded by Sextus Empiricus in Outlines of Scepticism in the following aspects: the investigative, non-dogmatic attitude towards the truth, the ability to set out oppositions and to realise the equipollence in opposed accounts of the truth, suspension of judgement, and the goal of tranquility. It also speculates on the implication of the common medical background Sextus and Keats shared by linking the ethical values of ancient scepticism to the humanitarian concerns of medicine that might have shaped Keats's scepticism. Although the connection between Keats, Sextus, and medicine is speculative, Burton's Anatomy of Melancholy – carefully studied by Keats – mentions Sextus, from which we can assume Keats's exposure to Sextan scepticism. The Renaissance revival of Pyrrhonian scepticism provides us with stronger evidence about its indirect influence on Keats through Montaigne and Shakespeare as its important inheritors.